The role of the teacher in developing educational values among secondary school students Idry School is a model (Journal of Human Sciences, 2024)
The research aimed to identify the role of the teacher in   developing educational values among secondary school students from their point of view.   Identifying the difference between the average scores of the sample members on the role of the teacher in developing educational values is attributed to the research variables  (Gender, student specialty, teacher specialty) For the purpose of achieving the goal of the research, the researcher designed a tool whose apparent validity and reliability was confirmed and was distributed to a sample of 102 male and female students. The research population included secondary school students in the Edre region, and she used the descriptive analytical approach. To describe and analyze the phenomenon, the researcher reached several results through the questionnaire paragraphs, namely that all teachers seek to develop educational values for students in the middle school certificate, where high averages were obtained. There are no statistically significant differences regarding the role of the teacher in developing educational values. The secondary school students in the Edre area, from their point of view. There are no statistically significant differences regarding the role of the  teacher in developing educational values among secondary school students in the Idri region from their point of view due to the student’s specialization variable. There are statistically significant differences regarding the role of the teacher in developing educational values among students The secondary certificate in the Idri region, from their point of view, is due to the teacher’s specialization variable, and these differences are in favor of Arabic language teachers.